A Preliminary Investigation of EFL Students' Intention to Use ChatGPT: A Structural Equation Modelling - Paulus Widiatmoko (Indonesia Technology Enhanced Language Learning (iTELL) Association, 2025)
This study is encouraged by pervasive advocacy for generative AI, despite emerging debates on their ethical concerns and use in academic environments. The research explores a model assesssing students’ beliefs and intentions to use ChatGPT. Utilizing the framework of Behavioral Reasoning Theory (BRT) and the Extended Theory of Planned Behavior (TPB), a post-positivist research design was employed. Overall model validity and reliability was gained along with dynamic correlation between variables in the model, including behavioral beliefs, perceived usefulness, social influence, perceived behavioral control and ethical considerations. In addition, this study suggests empirical data for the predictive power of beliefs and intention. As a pilot study, this research offers significant roles of motivational drives to use ChatGPT affecting students’ beliefs of the technology. Moreover, initial insights on the significant effects of demotivating factors to use the technology towards the participants’ subjective norms could be further explored in subsequent studies.